Evaluación de la tasa de crecimiento de progenies del cruce entre “tilapia roja” y “tilapia gris” de Oreochromis niloticus. - Quiroz Valderrama, Marco Antonio (2015)
This paper aims to estimate the growth rate of progeny from a cross between "red tilapia" and "gray tilapia" Oreochromis niloticus. Breeding ratio were conditioned in two females with a male in hapas to obtain progenies. Crossings were made ♂gray x gray♀, ♂gray x red♀, ♂red x gray♀ and ♂red x red♀. Progenies from maintained in hapas and after 2 months of breeding individuals of uniform size were selected and 10 individuals were placed hapa to assess the growth rate in all progenies every 2 weeks for 45 days, then was grouped to 2 people for 21 days taking data every week. The growth rate was higher for hybrids when the male parent was followed by the red cross when the male offspring was gray on ♂gray x gray♀ and cross ♂red x red♀.